Evaluasi Sisa Material Pada Pembangunan Gedung Kantor Kejaksaan Tinggi Jambi - Jufli Triyandi; Annisaa Dwiretnani; Ari Setiawan (Universitas Batanghari Jambi, 2022)
In the Jambi High Prosecutor's Office Building Construction Project, remnants of project materials were found. Waste material is one of the serious problems in the implementation of construction projects. Therefore, it is necessary to do a careful and precise calculation in determining the amount of material needed to be used in the project as well as an evaluation of the use of these materials. The aim of this research is; calculate the largest percentage of material waste costs during project implementation, identify the causes of material waste, and find ways to minimize material waste after conducting analysis and evaluation. The method used is a sociological juridical type, which is a type or type of research that emphasizes field research. To obtain data in the field by conducting interviews with the project supervisory consultant and data on images and photos of the project. The result of the observation of processed data is that the largest percentage of residual material costs is obtained from the concrete coral material with the highest percentage of 26.553% of the total cost of the remaining material. As for the causes of material remnants on the job, the first is coming from the factor of throwing or throwing material, workers in the field often throw material such as when casting columns and beams where a lot of concrete is wasted out of the formwork, another cause occurs in the skill factor Based on the skills of workers, there are some remnants of boards from making formwork on columns and beams. And also when cutting iron, a lot of iron can't be reused because the rest of the iron that is cut is too small. The conclusion is that there is residual material in this project from the factor of throwing or throwing material carried out by workers and on the skill factor of the worker.